The Effect of the Acupuncture Therapy in Combination with Soyeom Pharmacopuncture Therapy on the Improvement of the Symptoms of the Patients with Herniated Intervertebral Disk of L-spine in His Initial Stage of Hospitalization - Song Hyong-gun; Choi Joo-young; Kang Jae-hui; Lee Hyun (Korean Pharmacopuncture Institute, 2009)
Objectives: Herniated Intervertebral Disk(HIVD) of L-spine is one of the most common diseases that cause back pain and radiating pain. The aim of this study is to find out if the acupuncture therapy combined with Soyeom Pharmacopuncture therapy can improve the symptoms of the patients suffering from the disease more effectively than the acupuncture only therapy. Methods: We separated 30 patients into two groups. Group A was treated with the acupuncture only therapy, and Group B was treated with Soyeom Pharmacopuncture therapy in addition to the acupuncture therapy. We have observed patients for 7 days. We checked the Visual Analog Scale(VAS) for 4 times and did Straight Leg Raising Test(SLRT) twice. Results: 1. For 7 days from the admission day, the VAS score has been decreased significantly in both Group A and Group B. 2. For 7 days from the admission day, the VAS score of Group B has been appeared signifi cantly lower than that of Group A, so that we can know that patients in Group B has more rapidly improved than patients in Group A 3. From the admission day to the 3rd hospital day, the improvement index of VAS scroe of Group B has appeared significantly higher than that of Group A, but after 5th hospital day, there was no significance between the improvement index of VAS score of Group A and that of Group B. 4. For 7 days from the admission day, the SLRT(degree) has been improved significantly in both Group A and B, but there was no significance between the SLRT(degree) of Group A and that of Group B. Conclusion: We can use Soyeom Pharmacopuncture therapy with acupuncture therapy to make the patients suffering from back pain and radiating pain improve more rapidly.